KAJIAN META ANALISIS ALAT UKUR INTERNET GAMING DISORDER - Fiscarina, Claudia; Soetikno, Naomi; Idulfilastri, Rita Markus (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2020)
Online game addiction is one of the addictive behaviors described by APA (2013) as a mental and behavioral disorder called Internet Gaming Disorder (IGD) with 9 criteria. This study aims to identify the appropriate criteria for internet gaming disorder to be used in the preparation of measuring instruments using a meta-analysis study. A total of 33 out of 470 articles involving 11 measuring instruments for internet gaming disorder were studied using random-effect models. A total of 29599 samples were involved in this study. The results showed that the criteria for internet gaming disorder owned by the PVP Scale had a weighted score percentage of 10.3% with the criteria of preoccupation, tolerance, loss of control, withdrawal, escape, deception, and disregard family / school disruption, from the correlation coefficient test it showed that preoccupation (p 0.040 <0.05) and tolerance (p 0.043 <0.05) had a positive correlation with internet gaming disorder. This study did not show publication bias. Kecanduan game online merupakan salah satu dari perilaku kecanduan berdasarkan APA (2013) dijelaskan sebagai gangguan mental dan perilaku dengan sebutan Internet Gaming Disorder (IGD) dengan 9 kriteria. Penelitian ini bertujuan untuk mengidentifikasi kriteria internet gaming disorder yang tepat untuk dipergunakan dalam penyusunan alat ukur dengan studi meta-analisis. Sebanyak 33 artikel dari 470 artikel yang melibatkan 11 alat ukur internet gaming disorder dipelajari menggunakan random-effect models. Sebanyak 29599 sampel dilibatkan dalam penelitian ini. Hasil penelitian menunjukkan bahwa kriteria internet gaming disorder yang dimiliki oleh PVP Scale memiliki presentase weighted score sebesar 10.3% dengan kriteria preoccupation, tolerance, loss of control, withdrawal, escape, deception, and disregard family / school disruption. Dari uji koefisien korelasi pada ketujuh kriteria internet gaming disorder menunjukkan bahwa preoccupation (p 0.040 < 0.05) dan tolerance (p 0.043 < 0.05) memiliki korelasi positif terhadap internet gaming disorder.  Studi ini tidak menunjukkan bias publikasi.